Subclonagem e expressão do domínio catalítico da jararagina: estudo do efeito das modificações pós-traducionais na atividade hemorrágica - Sánchez, Liliana Torcoroma García (Universidade Federal de São Carlos, 2004)
Metalloproteases are Zn++-dependent peptidase enzymes, richly found in Crotalidae and Viperidae snake venoms. Most snake venom metalloproteases (svMPs) are active on extracellular matrix components and this effect is thought to result in bleeding as a consequence of the basement membrane disruption in capillaries. Jararhagin is a hemorrhagic svMP from Bothrops jararaca venom. This enzyme has proteolytic activity on fibrinogen and fibronectin and inhibits collagen-induced platelet-aggregation in vitro. Its amino acid sequence corresponds to a N-terminal metalloprotease domain, a disintegrin-like and a C-terminal Cysteine-rich, being classified as a P-III snake venom metalloprotease (svMP). This work describes the expression, purification and successful refolding of the recombinant catalytic domain of jararhagin. The heterologous protein was produced in E.coli, an in vivo expression system that does not make post-translational modifications. The recombinant refolded protein did not show any hemorrhagic activity in mice skin, as well as, the native deglycosylated jararhagin. However, they preserved their proteolytic activity on fibrinogen and fibronectin. It seems that the hemorrhagic properties of these hemorrhagins are dependent on post-translational modifications, whereas their proteolytic activity is not completely dependent on such modifications.
Keywords: Genética experimental; Veneno de serpente; Clonagem; Jararagina; Metaloproteases; CIENCIAS BIOLOGICAS::GENETICA